Moisture sorption characteristics of probiotic‐fermented sea tangle powder and its thermodynamic properties. Issue 7 (10th May 2019) - Yu, Daeung; Kwon, Gicheol; Kim, Moojoong; Kim, Young‐Mog; Choi, Soo‐Im; Kim, Gun‐Hee; Chung, Donghwa
Abstract: The moisture sorption characteristics of Lactobacillus brevis ‐fermented sea tangle powder were investigated. Moisture sorption isotherms were prepared at 4, 25, and 37°C in a water activity ( aw ) range of 0–0.96 and exhibited typical J‐shaped type III sorption characteristics, most likely due to the high carbohydrate content (65.7%) of the powder. The fermented sea tangle powder had greater moisture sorption capacity than those reported for other seaweeds, and changed to rubbery or liquid states when stored at aw > 0.5. The Peleg and GAB models accurately described the sorption isotherms, and the monolayer moisture contents were 0.176–0.443 g water/g dry matter. The moisture sorption was an exothermic, enthalpy‐driven, spontaneous process, and the enthalpy–entropy compensation existed with an isokinetic temperature of 448.1 K. The net isosteric heat of moisture sorption exponentially decreased from 15.02 to 0.49 kJ/mol as the equilibrium moisture content increased from 0.02 to 1.29 g water/g dry matter. Practical applications: Sea tangle is known to possess various biological and nutraceutical properties, such as antitumor and anticoagulant, antiproliferative, and antioxidant activities, which is commercially available in Pacific and Asian countries as a traditional functional food. The present study investigating information of moisture sorption characteristics of L. brevis ‐fermented sea tangle powder will be useful to understand its strongly hygroscopic nature and resulting low storage stability, which limits the easy and convenience of its handling and application. The information also will be important for improving its shelf life and retaining quality across postharvest processing.